2011
DOI: 10.1590/s0004-28032011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Does low dose13C-urea breath test maintain a satisfactory accuracy in diagnosing Helicobacter pylori infection?

Abstract: -Context -The standard doses of 13 C-urea in 13 C-urea breath test is 75 mg. Objective -To assess the diagnostic accuracy of 13 C-urea breath test containing 25 mg of 13 C-urea comparing with the standard doses of 75 mg in the diagnosis of Helicobacter pylori infection. Methods -Two hundred seventy adult patients (96 males, 174 females, median age 41 years) performed the standard 13 C-urea breath test (75 mg 13 C-urea) and repeated the 13 C-urea breath test using only 25 mg of 13 C-urea within a 2 week interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…13 C‐UBT, a noninvasive, nonradioactive method and considered the gold standard in monitoring H. pylori status after eradication therapy , was performed in this study. Briefly, one study in China had shown that the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of 13 C‐UBT with citric acid (96.5, 97.7, 98.2, 95.6, and 97.0%) were similar to 13 C‐UBT without a test meal (94.7, 97.7, 98.2, 93.5, and 96.0%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 C‐UBT, a noninvasive, nonradioactive method and considered the gold standard in monitoring H. pylori status after eradication therapy , was performed in this study. Briefly, one study in China had shown that the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of 13 C‐UBT with citric acid (96.5, 97.7, 98.2, 95.6, and 97.0%) were similar to 13 C‐UBT without a test meal (94.7, 97.7, 98.2, 93.5, and 96.0%).…”
Section: Methodsmentioning
confidence: 99%
“…So citric acid was not administered pretest Eradication of H. pylori infection was defined as when 13 C-UBT was negative 4 weeks after the completion of eradication therapy [21]. The delta over baseline below 4& cutoff was considered to be H. pylori-negative [21,38,40].…”
Section: Randomization and Eradication Therapy For H Pylori Infectionmentioning
confidence: 99%
“…Citric acid solution instead of juice showed high sensitivity (89.1%-100%) and specificity (100%) with low concentrations of 10 to 25 mg 13 C-urea solution (8) . Conversely, exam performed with 25 mg 13 C-urea solution in orange juice had lower sensitivity and specificity, and was not recommended for the clinical setting in our country (5) . Previously was shown that even after 7-day treatment with omeprazole, no patients had false negative results with the tablet based breath test (two tablets of 50 mg 13 C-urea and 463 mg citric acid) (13) .…”
Section: Discussionmentioning
confidence: 86%
“…The dose of 13 Curea administered is between 50 mg and 100 mg, and 75 mg is the dose most commonly used currently (11) . Studies have shown that doses above 125 mg are unnecessary (32) , and a dose of 25 mg is inefficient to provide good accuracy (33) . The interval of 15min instead of 30 min as optimal breath sampling after ingestion of the substrate has been considered sufficient to avoid interference of the pharyngeal flora with the possible presence of ureaseproducing bacteria and sufficient to allow hydrolysis 13 C-urea by contact with the preformed urease by H. pylori.…”
Section: Resultsmentioning
confidence: 99%